Chaos and nonlinear dynamics:an introduction to scientists and engineers - Hilborn, Robert C; Hilborn, Robert C (New Delhi, Oxford University Press, 2000)
Using a step-by-step introduction to dynamics and geometry in state space as the central focus of understanding nonlinear dynamics, this book includes a thorough treatment of both differential equation models and iterated map models (including a derivation of the famous Feigenbaum numbers). Chaos and Nonlinear Dynamics introduces students, scientists, and engineers to the full range of activity in the rapidly growing field on nonlinear dynamics. Using a step-by-step introduction to dynamics and geometry in state space as the central focus of understanding nonlinear dynamics, this book includes a thorough treatment of both differential equation models and iterated map models. It is the only book at this level to include the increasingly important field of pattern formation and a survey of the controversial questions of quantum chaos. Important tools such as Lyapunov exponents and fractal dimensions are treated in detail. With over 200 figures and diagrams, and analytic and computer exercises for every chapter, the book can be used as a course-text or for self-instruction. This second edition has been restructured to make the book even more useful as a course text many of the more complex examples and derivations have been moved to appendices. The extensive collection of annotated references has been updated through January 2000 and now includes listings of World Wide Web sites at many of the major nonlinear dynamics research centers. Key Features Comprehensive introduction to all aspects of nonlinear dynamics. Features a gradual introduction of all important concepts in nonlinear dynamics and its applications. Covers full range of contemporary activity in nonlinear dynamics. Contains extensive explanations and examples. Extensive use of good illustrations. About The Author: Robert C. Hilborn Department of Physics and Astronomy, University of Nebraska-Lincoln Table Of Contents First Edition Preface. First Edition Ackno
Includes bibliographical references.; Appendices A-J, 533-604p.; References 605-642p.; Index 643-650p.
Keywords: Chaos; Nonlinear dynamics; Physics